Influence of correlation between HLA-G polymorphism and Interleukin-6 (IL6) gene expression on the risk of schizophrenia. (July 2018) - Shivakumar, Venkataram; Debnath, Monojit; Venugopal, Deepthi; Rajasekaran, Ashwini; Kalmady, Sunil V.; Subbanna, Manjula; Narayanaswamy, Janardhanan C.; Amaresha, Anekal C.; Venkatasubramanian, Ganesan
Highlights: Interleukin-6 is implicated in schizophrenia pathogenesis. Maternal Immune Activation (MIA) can lead to interleukin-6 elevation. Human Leukocyte Antigen-G (HLA-G) can influence MIA. HLA-G polymorphism and IL-6 gene expression were examined in schizophrenia patients. HLA-G (14 bp Del/Del) could influence IL-6 mediated inflammation in schizophrenia. Abstract: Converging evidence suggests important implications of immuno-inflammatory pathway in the risk and progression of schizophrenia. Prenatal infection resulting in maternal immune activation and developmental neuroinflammation reportedly increases the risk of schizophrenia in the offspring by generating pro-inflammatory cytokines including IL-6. However, it is not known how prenatal infection can induce immuno-inflammatory responses despite the presence of immuno-inhibitory Human Leukocyte Antigen-G (HLA-G) molecules. To address this, the present study was aimed at examining the correlation between 14 bp Insertion/Deletion (INDEL) polymorphism of HLA-G and IL-6 gene expression in schizophrenia patients. The 14 bp INDEL polymorphism was studied by PCR amplification/direct sequencing and IL-6 gene expression was quantified by using real-time RT-PCR in 56 schizophrenia patients and 99 healthy controls. We observed significantly low IL6 gene expression in the peripheral mononuclear cells (PBMCs) of schizophrenia patients (t = 3.8, p = .004) compared to the controls. In addition, schizophrenia patients carrying Del/Del genotype of HLA-G 14 bp INDEL exhibited significantly lower IL6 gene expression (t = 3.1; p = .004) than the Del/Ins as well as Ins/Ins carriers. Our findings suggest that presence of "high-expressor" HLA-G 14 bp Del/Del genotype in schizophrenia patients could attenuate IL-6 mediated inflammation in schizophrenia. Based on these findings it can be assumed that HLA-G and cytokine interactions might play an important role in the immunological underpinnings of schizophrenia.